ON THE MEAN DENSITY OF GALAXIES AND IDENTIFICATION OF STRUCTURES - Panko, E.; Flin, P. (Одеські астрономічні публікації, 2017)
We discuss the difficulty of detecting of galaxy structures when the Voronoi tessellation technique is applied to two dimensional data. The problem relates to the determination of the mean density of objects in an investigated field. For data originating from plates with different limiting magnitudes there are subregions with totally different galaxy densities in the different part of investigated field. As a result galaxy structures being more numerous in more populated regions. The described effect is a general one, since all wide-field optical surveys have been made from plates with different magnitude limits.